PERDAGANGAN PEREMPUAN DAN ANAK SEBAGAI KEJAHATAN TRANSNASIONAL - Prasetia, Yudhya (Yustitia, 2021)
Organized crime in the transnational trafficking of women and children is a serious and farreaching crime and can even be classified as crimes against humanity as stated in the Rome Statute (1998) which regulates the permanent international criminal court. The objective of the provisions in protocol II is the criminal organization behind the trafficking of women and children, namely by punishing the perpetrators and protecting their victims, namely women and children. In the Palermo Convention2000) it is emphasized that the main objective is to enhance and strengthen cooperation between states parties in preventing and eradicating the five types of crimes which are the jurisdiction of the convention. This paper is the result of a research useing normative juridical approach by reviewing, and examining secondary data in the form of legislation, legal principles, and cases relating to the problem regarding to the trafficking of women and children.